دلالة النهي عند الأصولیین - د ا رسة نظریة تطبیقیة: سورة النور أنموذجا - عبابة, الطاهر (University of Eloued-جامعة الوادي, 2014)
This research deals with the significance of inhibition for the jurisprudents. In its practical part, it focused on Surah An-Noor (The Light), starting the first chapter with the study of the significance of 'term' over 'meaning'. After defining instant (fawr) and inhibition and stating its various types, the research moved to deal with the significance of inhibition over repetition and the issue of the necessity of inhibition corruption. In the second chapter, the study started with a general introduction of Surah An-Noor stating its broad themes and some ordinances related to inhibition as fornication, slander, etc. Some decencies were mentioned as well like asking permission for entering, lowering the gaze, inhibiting the spread of obscenity and following Satan (the devil).
مذكرة ماستر
Keywords: دلالة النهى-الاصولين- سورة النور انموذجا; The significance of the prohibition - the fundamentalists - Surat Al-Nur as a model